دور الدين في سياسات أفريقيا جنوب الصحراء الكبرى (1990-2022) (Comprehensive Journal of Science, 2025)
This study examines the role of religion in politics in sub-Saharan African countries from 1990 to 2024, focusing on the relationship between religion and power and its role in stability or conflict. The research uses a descriptive analytical approach, historical review, and comparative analysis to understand the political impact of religion. Primary sources include official documents, political statements, books, and academic studies, and various research tools like analysis of political and religious discourses, interviews, and questionnaires. The sample includes academics, religious leaders, and political officials who participated in decision-making during the study period, Preliminary results show that religion played a dual role in politics, enhancing political legitimacy for some regimes and contributing to escalating religious and sectarian conflicts in some countries. Religious institutions were active in decision-making processes, either directly or indirectly, and their influence on regional cooperation or international polarization was also highlighted, the study concludes that achieving a balance between religion and politics in sub-Saharan Africa requires policies that promote religious dialogue and prevent the exploitation of religion in political conflicts.
Keywords: Religion, Politics, Sub-Saharan Africa, Political legitimacy, Religious conflicts, Religious institutions, Extremism, International relations.